Obstructive sleep apnea and abdominal aortic calcification: Is there an association independent of comorbid risk factors?. Issue 1 (July 2015) - Tachikawa, Ryo; Koyasu, Sho; Matsumoto, Takeshi; Hamada, Satoshi; Azuma, Masanori; Murase, Kimihiko; Tanizawa, Kiminobu; Inouchi, Morito; Oga, Toru; Mishima, Michiaki; Togashi, Kaori; Chin, Kazuo
Abstract: Background: No studies have addressed the relationship between obstructive sleep apnea (OSA) and abdominal aortic calcification (AAC), a marker for subclinical atherosclerosis and future cardiovascular events. Objectives: To investigate 1) the association between OSA severity and AAC, and 2) whether OSA can impact the extent of AAC independent of comorbid atherogenic risk factors. Methods: 390 participants aged 40–70 years underwent polysomnography and abdominal computed tomography. AAC was separately quantified in the upper and lower abdominal aorta using the modified Agatston scoring method, and the total AAC score was calculated as a sum of the two scores. OSA was defined as none/mild (apnea-hypopnea index [AHI] <15, n = 87), moderate (AHI 15–30, n = 129), and severe (AHI ≥30, n = 174). Results: Log-transformed total AAC score adjusted for age and body mass index (BMI) was greater in participants with an elevated AHI (3.4 for none/mild OSA, 3.7 for moderate OSA, and 4.2 for severe OSA, p = 0.04). Multivariate linear regression analysis including age and BMI as covariates showed that severe OSA was associated with higher scores for the lower and total AAC (β = 0.15 and 0.14, p = 0.01 and 0.01, respectively). The association did not persist after additionally adjusting for traditional atherogenic risk factors including visceral fat, smoking, hypertension, dyslipidemia, and diabetes. Conclusions: Severe OSA was associated with a greater extent of AAC, which was dependent on coexisting atherogenic risk factors. Comorbid cardiometabolic disorders may largely mediate the association of OSA with subclinical atherosclerosis. Highlights: We examine the association between OSA severity and abdominal aortic calcification. Abdominal aortic calcification increases in severe OSA. Traditional risk factors are more potent to increase aortic calcification than OSA. OSA may enhance atherosclerosis mainly through comorbid cardiometabolic disorders.